2020
DOI: 10.1016/j.sdentj.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of forensic odontology and willingness to enroll in a prospective dental registry: A survey conducted in Saudi Arabia

Abstract: BackgroundThe establishment of a national dental registry provides a great opportunity for the healthcare and criminal investigation systems. Its feasibility would rely mainly upon public knowledge and a willingness to contribute dental profiles. The aim of this study was to evaluate the level of awareness among the Saudi public of forensic odontology and to evaluate their willingness to participate in a prospective national dental registry.MethodsA cross-sectional survey based on a self-administered survey qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…13 This contradicts research carried out in Saudi Arabia where the majority of people in Saudi Arabia do not know that forensic odontology helps in medico-legal cases. 8 In this survey, the majority of respondents did not know that forensic odontology can help in cases of sexual harassment and violence. A systematic review paper revealed that a large proportion of the public has insufficient knowledge of the ability of forensic odontologists to handle cases of abuse.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…13 This contradicts research carried out in Saudi Arabia where the majority of people in Saudi Arabia do not know that forensic odontology helps in medico-legal cases. 8 In this survey, the majority of respondents did not know that forensic odontology can help in cases of sexual harassment and violence. A systematic review paper revealed that a large proportion of the public has insufficient knowledge of the ability of forensic odontologists to handle cases of abuse.…”
Section: Discussionmentioning
confidence: 94%
“…This contrary to research conducted in Saudi Arabia, the majority of respondents did not know that the palatine rugae and tooth characteristics were different for each individual. 8 In the survey it was found that the majority of respondents knew that forensic odontology helped in medico-legal cases, identifying accident victims and investigating bite marks. This survey is in line with the empirical role of forensic odontologists in disaster management and victim identification by maintaining well-structured, comprehensive and accurate dental records for teaching and research purposes, as well as for legal matters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations